Evaluation of a new way to assess mid-parental height (mph) and the relative impact of mph on clinical judgment. (24th May 2012) - Wright, CM; Cole, TJ
Abstract : Background and aims: Mid-parental height (MPH) is important for the assessment of short stature, but the calculation of target height (TH) is complex. As part of the design of new UK school age charts, a familial height scale (FHS) has been developed which allows MPH to be read off and compared to predicted adult height (Ann Hum Biol 2011;38:662-8) without calculation. We aimed to evaluate users' understanding of this feature and the impact of MPH on clinical judgement. Method: A questionnaire was completed in two workshops with medical students (N=20) and by paediatricians at two scientific meetings (N=40). The questionnaire presented four standardised scenarios with growth data (see table 1 ). These were permutated through two questionnaire versions, with each respondent viewing two plotted scenarios using TH and two on FHS. For each scenario the respondent was asked to rate the chance that the child's growth was abnormal after viewing the growth chart then after seeing parental height data. Respondents were then asked to rate the two scales in terms of ease of use, understandability and time to complete (medical students only). Results: Respondents found the FHS easier to use (mean (SD) difference 0.9 (1.2); p <0.001). Paediatricians found it easier to understand (0.5 (1.3); P=0.03); medical students did not, but they rated FHS as quicker to complete (1.8 (1.2); P<0.001). Both methods produced very similar interpretations. Respondents were much more concerned about a discrepancy from parental height than slow growth. Conclusions: The FHS simplifies the comparison of child to parental heights and is generally preferred to TH. A discrepancy from MPH is rated as more likely to reflect abnormal growth than a decline in growth itself, suggesting that MPH assessment could offer false reassurance.